Improve the insulation performance of air‐insulated gaps: Application of polyurea materials on the ground potential side of transmission line - Le Li; Huajie Shen; Zhongyuan Zhang; Shijie Xu; Yifan Liu; Haishun Zhang; Li Tang; Honggang Peng; Fan Wang; Guangxi Li; Haoyi Li; Yunpeng Liu (High Voltage)
Abstract The authors aim to explore the effectiveness of two‐component polyurea materials applied to transmission line towers (on the ground potential side) in improving the insulation performance of the conductor–tower gap. The physicochemical and electrical properties of the polyurea materials were first analysed and a conductor–tower gap testing platform was constructed to investigate the effects of the length and thickness of the polyurea layer on the ground potential side under a 50‐Hz AC voltage on the breakdown characteristics. Experimental studies revealed that the characteristic breakdown voltages of polyurea layers of different lengths (40, 100, 200, and 400 cm) are approximate. Compared with the air‐insulated gap before the application of polyurea, thinner polyurea layers (1 and 2 mm) showed no significant improvement in the breakdown voltage, whereas thicker layers (3, 4, and 5 mm) significantly improved it. In particular, with a polyurea layer thickness of 4 mm and gap distance of 20 cm, the characteristic breakdown voltage increased from 138.43 to 155.71 kV. In addition, the withstand voltage distance decreased from 4 to 3 cm without any breakdown, even when the high‐voltage conductor directly contacted the polyurea layer and the layer was not penetrated. The authors provide theoretical support and experimental data for improving the conductor–tower gap insulation performance by applying a polyurea layer on the ground potential side.